Experiences with a researcher-centric ELN. Issue 3 (3rd November 2014) - Badiola, Katrina A.; Bird, Colin; Brocklesby, William S.; Casson, John; Chapman, Richard T.; Coles, Simon J.; Cronshaw, James R.; Fisher, Adam; Frey, Jeremy G.; Gloria, Danmar; Grossel, Martin C.; Hibbert, D. Brynn; et al.
Abstract : Chemical scientists' experiences with LabTrove. Abstract : Electronic Laboratory Notebooks (ELNs) are progressively replacing traditional paper books in both commercial research establishments and academic institutions. University researchers require specific features from ELNs, given the need to promote cross-institutional collaborative working, to enable the sharing of procedures and results, and to facilitate publication. The LabTrove ELN, which we use as our exemplar, was designed to be researcher-centric ( i.e., not only aimed at the individual researcher's basic needs rather than to a specific institutional or subject or disciplinary agenda, but also able to be tailored because it is open source). LabTrove is being used in a heterogeneous set of academic laboratories, for a range of purposes, including analytical chemistry, X-ray studies, drug discovery and a biomaterials project. Researchers use the ELN for recording experiments, preserving data collected, and for project coordination. This perspective article describes the experiences of those researchers from several viewpoints, demonstrating how a web-based open source electronic notebook can meet the diverse needs of academic researchers.